The Evaluation of the Indonesian Government Authority in Managing the Border Area of West Kalimantan-Sarawak - Muhammad Syafei; Muhammad Rafi Darajati; Adityo Darmawan Sudagung (International Journal of Environment, Architecture, and Societies, 2023)
This article aims to analyse the extent to which the regulatory authority established by Law Number 43 of 2008 has been implemented to manage the development of Indonesia’s border areas. The central and regional governments envision the forefront of the state to optimise the welfare of people living in Indonesia's border areas with neighbouring countries. Due to the widening economic gap with Sarawak, less optimal coordination between central and regional governments in handling state border areas, and limited infrastructure and social facilities, the border area poses a complex threat to the sovereignty of Indonesia. We conducted descriptive normative research by exploring several sources from the laws and regulations, books, journal articles, and online news articles. Additionally, we incorporated field research as our data collection method in West Kalimantan Province. The author observed the border area and conducted expert interviews with the local government, the manager of the border gate at Entikong, Sanggau Regency, and the West Kalimantan Provincial government representative. Normatively, the authority has been divided and defined in Law Number 43 of 2008. However, a lack of coordination in implementing the law was caused by the ambiguous hierarchy of authority among the stakeholders due to the physical capabilities to reach the areas. We argue that the closest coverage of authoritative bodies in giving services to the people will boost the people’s welfare in the border areas.